Estudo e aplicação do grafeno como biossensor - Leonel Muniz Meireles (2016)
Graphene have emerged as an important tool for use and study in biosensor. With only one atom thick, its surface area/volume ratio is very large, combined with unique electronic properties, graphene is extremely sensitive to changes on its surface, which makes it a promising template for probing biological systems. In this work, we strive to improve the understanding of graphene as sensor material, by conducting a study to develop different detection approaches. We execute, as a proof of concept, the fabrication of devices in a field-effect transistor architecture (FET) using graphene as the conductor channel and appling a gate voltage via an electrochemical solution. We explored three types of devices: pH biosensor, the acetylcholine biosensor and the ant-HSA biosensor. In acetylcholine sensors and ant-HSA sensors, the graphene was functionalized with PBSE + acetylcholinesterase and PBSE + HAS respectively. For pH sensors, the graphene not was functionalized. Our experiments consists to verify the evolution of the electrical properties of functionalized graphene when it comes in contact with anti-HSA at different concentrations (ant-HSA sensor), with acetylcholine (acetylcholine sensor) and evolution of electrical graphene properties when in contact with PBS (phosphate buffered saline) at different pH (pH sensor). The results show that graphene, without functionalization, is sensitive to change of pH solution in a variation of 25 mV/pH. This result is important for the interpretation and understanding of the sensing mechanism acetylcholine biosensor, which was able to detect acetylcholine in a concentration of 3.33 mmol/L. The functionalized graphene device PBSE + HSA detected anti-HSA at a concentration of 3.33 mmol/L. In addition, measurements were performed to characterize the influence of functionalization of graphene. For each result, we performed a discussion of the sensing mechanism for each device.